PENGOLAHAN MINYAK JELANTAH MENJADI LILIN AROMATERAPI DI DESA KEMIRI SIDOARJO: SOLUSI KREATIF UNTUK LINGKUNGAN DAN EKONOMI LOKAL: PENGOLAHAN MINYAK JELANTAH MENJADI LILIN AROMATERAPI DI DESA KEMIRI SIDOARJO: SOLUSI KREATIF UNTUK LINGKUNGAN DAN EKONOMI LOKAL - Budi Prabowo; Devi Diyah Ayu Prameswari; Laila Krisna Arti; Wandah Nur Aliyyah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Careless disposal of waste can pollute the surrounding aquatic ecosystem. Therefore, innovative steps and solutions are needed to avoid random waste disposal in the environment around the community. Cooking activities that are carried out every day will definitely leave behind unused ingredients, one of which is cooking oil that has been used for frying activities. This cooking oil will become dangerous waste if thrown away carelessly. As a form of community service, group 5 of the National Defense KKN-T Wave 1, UPN